Altered erythropoiesis and iron metabolism in carriers of thalassemia. (11th November 2014) - Guimarães, Jacqueline S.; Cominal, Juçara G.; Silva‐Pinto, Ana Cristina; Olbina, Gordana; Ginzburg, Yelena Z.; Nandi, Vijay; Westerman, Mark; Rivella, Stefano; de Souza, Ana Maria
Abstract The thalassemia syndromes (α‐ and β‐thalassemia) are the most common and frequent disorders associated with ineffective erythropoiesis. Imbalance of α‐ or β‐globin chain production results in impaired red blood cell synthesis, anemia, and more erythroid progenitors in the blood stream. While patients affected by these disorders show definitive altered parameters related to erythropoiesis, the relationship between the degree of anemia, altered erythropoiesis, and dysfunctional iron metabolism has not been investigated in both α‐thalassemia carriers (ATC) and β‐thalassemia carriers (BTC). Here, we demonstrate that ATC have a significantly reduced hepcidin and increased soluble transferrin receptor levels but relatively normal hematological findings. In contrast, BTC have several hematological parameters significantly different from controls, including increased soluble transferrin receptor and erythropoietin levels. These changes in both groups suggest an altered balance between erythropoiesis and iron metabolism. The index sTfR/log ferritin and (hepcidin/ferritin)/sTfR are, respectively, increased and reduced relative to controls, proportional to the severity of each thalassemia group. In conclusion, we showed in this study, for the first time in the literature, that thalassemia carriers have altered iron metabolism and erythropoiesis.